Reverse logistics system and recycling potential at a landfill: A case study from Kampala City. (August 2015) - Kinobe, J.R.; Gebresenbet, G.; Niwagaba, C.B.; Vinnerås, B.
Highlights: Quantifies the different waste streams delivered at the landfill. Evaluates the amount of potential waste products that enters into the reverse cycle. Drawing out the reverse logistics activities from Kampala City to Kiteezi landfill. Identify the storage, collection and transportation mechanisms of products to the various destinations; and finally. The study suggests efficient measures to improve reverse logistics system. Abstract: The rapid growing population and high urbanisation rates in Sub-Saharan Africa has caused enormous pressure on collection services of the generated waste in the urban areas. This has put a burden on landfilling, which is the major waste disposal method. Waste reduction, re-use and recycling opportunities exist but are not fully utilized. The common items that are re-used and re-cycled are plastics, paper, aluminum, glass, steel, cardboard, and yard waste. This paper develops an overview of reverse logistics at Kiteezi landfill, the only officially recognised waste disposal facility for Kampala City. The paper analyses, in details the collection, re-processing, re-distribution and final markets of these products into a reversed supply chain network. Only 14% of the products at Kiteezi landfill are channeled into the reverse chain while 63% could be included in the distribution chain but are left out and disposed of while the remaining 23% is buried. This is because of the low processing power available, lack of market value, lack of knowledge and limited value addition activities to the products. This paper proposes possible strategies of efficient and effective reverse logistics development, applicable to Kampala City and other similar cities.